Implementasi AI (Chat GPT) dalam Pembelajaran Bahasa Indonesia di SMK Amanah Makassar - Runimeirati; Risal, Andi Alviadi Nur; Arifin, Dafrid Cahyadi (Yayasan Habiburrahman Jamalu Bina Ummat, 2026)
This community service program aims to implement Artificial Intelligence (AI), specifically ChatGPT, in the teaching and learning process of Bahasa Indonesia at SMK Amanah Makassar. The program is designed to enhance the quality of learning through technology-based assistance that supports students in understanding lessons, expanding vocabulary, and improving writing, analytical, and critical thinking skills. The implementation methods include socialization of AI utilization, training sessions for teachers and students, classroom practice using ChatGPT as a learning tool, and evaluation of learning outcomes. The results indicate an increase in students’ learning motivation, interactive engagement in the classroom, as well as improvement in students’ writing performance, especially in producing structured and coherent texts. Additionally, teachers benefit from acquiring new competencies in integrating AI as a supportive instructional medium. This program is expected to serve as a sustainable model for implementing AI in education, particularly in Bahasa Indonesia learning at the vocational high school level..